2003
DOI: 10.1577/1548-8454(2003)65<126:sdilfc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Egg Disease in Landlocked Fall Chinook Salmon Eggs: Possible Causes and Therapeutic Treatments

Abstract: Soft‐egg disease was observed in the spawn from 5 of 15 landlocked fall chinook salmon Oncorhynchus tshawytscha from Lake Oahe, South Dakota, with the percentage of prematurely hatching fry per spawn ranging up to 42.0%. Soft‐egg disease was only identified in eggs collected from presumed 4‐year‐old salmon, and its occurrence is hypothesized to be at least partially caused by maternal dietary stress during egg development. Egg mortality after the appearance of soft‐egg symptoms was significantly less in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
0
18
1
Order By: Relevance
“…The greater tag returns per tank from the high-density tanks in the 2003 and 2004 stocking years indicate that in absolute terms, the total number of Chinook Salmon surviving after stocking could be enhanced by rearing at higher densities. However, this would likely only occur during years of favorable environmental conditions and only if the numbers of eggs and subsequent fry are not limited-unlike the typical situation for Lake Oahe Chinook Salmon (Barnes et al 2003;Wipf and Barnes 2012). In addition, to maximize poststocking returns at high densities, water flow to the rearing tanks cannot be limited and increased expenditures on fish food would likely be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The greater tag returns per tank from the high-density tanks in the 2003 and 2004 stocking years indicate that in absolute terms, the total number of Chinook Salmon surviving after stocking could be enhanced by rearing at higher densities. However, this would likely only occur during years of favorable environmental conditions and only if the numbers of eggs and subsequent fry are not limited-unlike the typical situation for Lake Oahe Chinook Salmon (Barnes et al 2003;Wipf and Barnes 2012). In addition, to maximize poststocking returns at high densities, water flow to the rearing tanks cannot be limited and increased expenditures on fish food would likely be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The Open Fish Science Journal, 2014, Volume 7 31 radically with landlocked fall Chinook salmon eggs incubated at McNenny [18] and has been observed in other salmonid hatcheries as well [19,20]. Barnes et al [18] indicated that formalin treatments provided some remediation against the lethal effects of soft-egg disease.…”
Section: Landlocked Fall Chinook Salmon Egg Survivalmentioning
confidence: 94%
“…Barnes et al [18] indicated that formalin treatments provided some remediation against the lethal effects of soft-egg disease. In 2012, approximately 10% of the eyed eggs died from eye-up to hatch in both the jars and trays that received daily formalin treatments.…”
Section: Landlocked Fall Chinook Salmon Egg Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies evaluated different iodine disinfection protocols in combination with regular treatments with formalin as an antifungal agent (Barnes et al . ; Chalupnicki et al . ; Pravecek & Barnes, ).…”
Section: Evaluation Criteria For a Successful Disinfectionmentioning
confidence: 99%